Effect of host age on searching and oviposition behaviour of Diaeretiella rapae (MIntosh) (Hymenoptera Aphidiidae) - Kant, R.; Sandanayaka, W.R.M.; He, X.Z.; Wang, Q. (New Zealand Plant Protection, 2008)
Diaeretiella rapae is an important biological control agent of cabbage aphid Host searching handling and oviposition behaviour were investigated in relation to host age The parasitoid spent 61 of her foraging time searching for hosts Host handling time of the parasitoid decreased with increased number of host encounters The females were more successful in finding older hosts (7 days old) and spent more time (949 205 s/encounter) and did more stings (99 14/encounter) on them than the younger hosts They preferred to sting the abdomen rather than the thorax head or legs of the host The average number of eggs laid per host was highest (14 02 eggs) in 7dayold hosts When attacking 7dayold hosts they gained 42 success in ovipositing the host compared to 10 18 and 30 success in 1 3 and 5dayold hosts respectively Results suggest that D rapae may have adaptive preference for larger hosts and mass production could be more efficient by using 7dayold aphids